On common fixed points of pairs of a single and a multivalued coincidentally commuting mappings in D-metric spaces - B. C. Dhage; A. Jennifer Asha; S. M. Kang (International Journal of Mathematics and Mathematical Sciences)
The present paper studies some common fixed-point theorems for pairs of a single-valued and a multivalued coincidentally commuting mappings in D-metric spaces satisfying a certain generalized contraction condition. Our result generalizes more than a dozen known fixed-point theorems in D-metric spaces including those of Dhage (2000) and Rhoades (1996).